Advancing school‐based interventions through economic analysis. Issue 141 (March 2014) - Olsson, Tina M.; Ferrer‐Wreder, Laura; Eninger, Lilianne
Abstract : Commentators interested in school‐based prevention programs point to the importance of economic issues for the future of prevention efforts. Many of the processes and aims of prevention science are dependent upon prevention resources. Although economic analysis is an essential tool for assessing resource use, the attention given economic analysis within school‐based prevention remains cursory. Largely, economic analyses of school‐based prevention efforts are undertaken as secondary research. This limits these efforts to data that have been collected previously as part of epidemiological and outcomes research. Therefore, economic analyses suffer from gaps in the knowledge generated by these studies. This chapter addresses the importance of economic analysis for the future of school‐based substance abuse prevention programs and highlights the role of prevention research in the development of knowledge that can be used for economic analysis.